Estilos de afrontamiento de un grupo de hombres frente al duelo por ruptura amorosa. (2023)
The purpose of this study is to describe the coping styles in the face of grief due to a love breakup that a group of men between 20 and 40 years old, residing in the city of Cali, have had a stable relationship for more than a year and that the breakup time does not exceed one year after completion. A structured interview is applied to describe the emotions and experiences that the separation has generated, and how they face this grieving process.